Diagnostic value of anti-GP2 antibodies determined in serum and coprofiltrates in children with inflammatory bowel disease - A. P. Toptygina; E. L. Semikina; S. V. Petrichuk; A. S. Potapov; Andrey N. Surkov (Медицинская иммунология, 2020)
Inflammatory bowel diseases (IBD), such  as Crohn’s disease (CD) and  ulcerative colitis (UC), are characterized by chronically recurring inflammation of intestinal wall and are associated with a significant decrease in the  quality  of life. A spectrum of genetic  variants  associated with  Crohn’s disease  is described. Intestinal dysbiosis (DB)  may be the triggering factor of the disease. Glycoprotein 2 (GP2), the main protein of pancreatic zymogen  granules, is secreted  into the intestines with digestive enzymes.  Anti-GP2 antibodies were found in the serum of patients with CD.  The aim of the present  study was to investigate  the levels of anti-GP2 antibodies in serum  and feces of children with IBD  compared with the DB group.  Serums  and coprofiltrates from 110 children (64 boys and 46 girls) at the age of 12.3 (2.6-17.9) years were studied; 36 patients with CD, 30 patients with UC.  A comparison group consisted of 44 patients with DB. IgG and IgA antibodies against GP2 were tested with ELISA. Nonparametric statistics methods are applied, the results are presented as percentages and medians (Me (Q0.25-Q0.75)). The serum levels of anti-GP2 IgA antibodies were 9.97 (3.35-13.45) U/ml for the CD patients, 6.08 (2.71-14.26) U/ml for UC and 2. 94 (2.29-6.41) U/ml for DB. The levels of anti-GP2 IgG antibodies in serum were 6.16 (3.26-18.4) U/ml for CD, 5.26 (2.97-7.52) U/ml for UC, and for DB 5.23 (2.53-8.85) U/ml. The cut-off  threshold concentration for anti-GP2 IgG antibodies was 13.8 U/ml, with sensitivity of 63.2%, specificity 100%, and for IgA 5.63 U/ml, with sensitivity of 60.5% and specificity of 78.8%, thus being lower than the calculated cut-off  for adults (20 U/ml). The levels of anti-GP2 IgG in coprofiltrates in children of comparison group  were 1.99 (1.26-3.04) U/ml; in the  patients with CD, 23.5 (16.15-29.3) U/ml, and  in children with UC, 20.45 (13.63-25.5) units/ml (p < 0.001). The cut-off  value amounted 8.0 U/ml, with 100% sensitivity  and  100% specificity.  Concentrations of anti-GP2 IgA in coprofiltrates of patients with IBD  did not significantly  differ from DB patients. Moreover, the concentration of sIgA in the coprofiltrates of patients with IBD  was significantly  higher than  their level in DB group. The anti-GP2 IgA/sIgA  ratio was significantly lower in patients with CD (0.326 (0.23-0.512)), and UC (0.327 (0.205-0.435)), than in patients with DB (2.332 (1.575-3.523)) (p < 0.001);  the cut-off  level was 0.784, with a sensitivity of 97.7% and specificity  of 98.6%. It is discussed, whether fecal anti-GP2 IgA antibodies should  be considered as protective, supporting intestinal homeostasis, whereas anti-GP2 IgG antibodies are pathogenetically significant  for development of IBD.  Thus, using a non-invasive method for determining anti-GP2 antibodies in stool, when exceeding the cut-off for IgG, and reduction of IgA/sIgA ratio below the cut-off, one may differentiate IBD from DB with a similar symptoms at the onset of disease, with 100% sensitivity and 100% specificity.